Detection of acute Lymphocytic Leukemia (ALL) and its type by image processing and machine learning - Chowdhury, Himadri; Banik, Shounak; Hossain, Arafat; Khaled, Md. Imran (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.